1990
DOI: 10.1002/bjs.1800770331
|View full text |Cite
|
Sign up to set email alerts
|

Infected false aneurysms in the groin of intravenous drug abusers

Abstract: The hazards of dealing with infected false femoral aneurysms resulting from intra-arterial narcotic injection are highlighted in six patients. Two patients were human immunodeficiency virus positive and three patients were hepatitis B surface antigen positive. Because of these infections exploration of groin swellings as presumed soft tissue abscesses is potentially hazardous without proper proximal vascular control. All patients underwent reconstruction following arterial ligation and five grafts became infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
7

Year Published

1992
1992
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 4 publications
1
54
0
7
Order By: Relevance
“…These organisms account for most isolates from aneurysmal sac or surrounding tissues in drug addicts with an IFA. [2][3][4][5]8,9,12,[15][16][17]19,21,25 The basic operative plan consisted of Lig-Exc of the IFA, Ld of all necrotic tissue, and extensive drainage of local sepsis, as well as wound cultures, irrespective of the anatomical position of the aneurysm. The feeding vessels were ligated in areas free of infection, far from the infected pseudoaneurysms, to prevent secondary bleeding from disintegration of the infected arterial wall.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These organisms account for most isolates from aneurysmal sac or surrounding tissues in drug addicts with an IFA. [2][3][4][5]8,9,12,[15][16][17]19,21,25 The basic operative plan consisted of Lig-Exc of the IFA, Ld of all necrotic tissue, and extensive drainage of local sepsis, as well as wound cultures, irrespective of the anatomical position of the aneurysm. The feeding vessels were ligated in areas free of infection, far from the infected pseudoaneurysms, to prevent secondary bleeding from disintegration of the infected arterial wall.…”
Section: Methodsmentioning
confidence: 99%
“…Huebl and Read suggested that the inadvertent intra-arterial or periarterial injection of drugs is the primary cause of femoral false aneurysms. 10 Extravasation of blood and contamination of the subsequent hematoma follows, resulting in breakdown and rupture of the vessel wall, and eventually, an infected pseudoaneurysm 2,4,7,10,11,15,17,18 without surrounding adventitia. Cellulitis or abscess, produced by contaminated needles, can also produce vessel wall rupture if it is close to a vascular structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These infections were a major cause for morbidity and mortality (11). Because there is great risk for infection, it is suggested that ligation and debridement alone be carried out with immediate arterial reconstruction only for nonviability (12).…”
Section: Discussionmentioning
confidence: 99%